Development Finance Models and Sustainable Growth of Nigeria: A Granger Causality Approach - Erhijakpor, A.E.O.; Enebeli, I.A. (PT. Riset Press International, 2024)
One of the primary goals of policy makers is to build an economy that is relatively stable. As such, to ensure that the economy is relatively stable, policy makers embark on series of financial (economic) reforms. However, even with the concerted efforts to improve the state of the Nigerian economy, the Nigeria is still under-developed. Hence, the paper aimed at examining the effects of development finance on sustainable growth of Nigeria using the granger causality approach. The development finance measures are private sector credits, broad money supply (BMS), Interest rate volatilities, and trade openness while sustainable growth measured by RGDP. The study spanned from 1989 to 2021. The study reported that, both private credits and broad money supply bi-granger cause sustainable growth but trade openness only cause sustainable growth. However, Interest rate volatilities did not influence sustainable growth nor growth did. Hence, the paper concludes that, both private sector credits and broad money supply precedes growth just as growth precedes both private sector credits and broad money supply while trade openness is a precondition for economic growth. As such, it is imperative for the apex regulatory body to instruct Nigerian banks to give more credits to the private sector. Lastly, the efforts should be made to improve the degree to which the Nigerian economy is open to trade. Lastly, the rising high cost of borrowing should be reduced.